Objects of affection : the book and the household in late medieval England - Seaman, Myra (Manchester medieval literature and culture., 2021)
This study investigates the affective agency of the book, through the emotional literacy training that a single codex provided a late-medieval English household. It demonstrates how MS Ashmole 61 affirms both the physical and moral agency of nonhumans, who fashion spiritually generous and socially mindful human household members.